Three-dimensional imaging of polymer materials by Scanning Probe Tomography - Alekseev, Alexander; Efimov, Anton; Loos, Joachim; Matsko, Nadejda; Syurik, Julia (My University, 2014)
Abstract Scanning Probe Tomography (SPT) is a new method for nanoscale volume imaging of sample morphology and property distribution based on Scanning Probe Microscopy (SPM). In this review we describe and discuss recent results obtained with different SPT techniques on polymer samples. The design of the existing SPM based instruments used for tomography in principle allows for volume reconstruction of any kind of mechanical, functional or chemical property distribution, which can be measured by SPM. We describe some recent volume reconstruction results from several types of polymer materials and critically discuss limitations and future prospects of SPM tomography.
Keywords: Scanning Probe Microscopy; Scanning Probe Tomography; Tomography; Three-dimensional reconstruction